TMCHUB a study of an effective design for UP TMC Web Portal - Gonzales, Mark Louie Francisco
The Internet has changed, and is still changing the way the world works. It is not just a fad that businesses and organizations have to ride in the bandwagon. On the contrary, it has done wonders to many organizations already. However, TMC is not yet maximizing the potential of its online presence. And that is the core of this project paper-to be able to maximize the use of its existing website (http://www.tmc.upd.edu.ph). Sections 1 and 2 introduce the project paper. These sections discuss the project background and the significance of this project. It also mentioned the inspiration of the proponent on how it arrived in this selected topic. The objective of this study is to identify the best design of the web portal. Design here is about the features and functionalities and not about aesthetics or making the web portal pleasing to the eyes. On the third section, this paper enlightens the understanding about the World Wide Web. It provided pointers on how to make a website effective. And these are to know the target audience, always provide them with something new, give them a good experience while surfers are browsing the website, and of course always make the website available where the audience are. Almost everybody surfing the net have heard about at least one among these popular social networking sites Friendster, MySpace, Facebook and Twitter. Still on the third section, the reasons behind the success of these websites are discussed. And to complete the section, it also includes observations on how the Internet is changing our lives-both in good ways and bad. The fourth part of this paper is about how this research was carried out. The design of this research is combination of description and analytical type. Also detailed in this section are the sources of information and these are the surveys and interviews with the TMC Staff, UPSTeM President, TMC Professors and an I.T. Consultant from the University of the Philippines Computer Center (UPCC). The data gathered and analyses of these were covered in the fifth section. Surveys are extracted from the students (both present and prospective) and alumni of the Center and play the big role in championing this website because they will be the ones that will populate it with information thru their discussion and sharing of literatures. One of the most prominent responses on all the surveys and the interviews is that of having a message board/forum on the web portal. And this fortunately, is possible with the current network infrastructure of UP. To summarize this paper, the last three sections are about the conclusion the proponent came up with based on his studies and analyses of the all the information gathered. The section also includes the sitemap of the proposed TMC Web Portal together with mock processes of how the added features will be operated. Finally, suggestions for further studies were also mentioned. These include the exploration of synching with UP database, incorporation of API with other social networking sites, and policies of copyrighted material (if it would still be under the doctrine of fair use to store copyrighted materials in the database).